Faktor yang Paling Mempengaruhi Siswa Atas Pilihan Perguruan Tinggi : Sebuah Penelitian Eksploratori - ROCHYATI . (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2015)
This paper aims to examine the important factors of various types of information for potential students when selecting a university. The data were collected from 202 respondents of students in year 1 at various university in Jabodetabek. The results reveals that students have five personal reasons when they choose HEI i.e. institution reputation, capacity development, facilities on campus, program suitability and tuition fee. The institution reputation emerges as the most important factor when students gather information to choose his or her future HEI. However, tuition fee is the most influential factor which affects student’s decision to enter the university.